2010
DOI: 10.2146/ajhp090506
|View full text |Cite
|
Sign up to set email alerts
|

Risks and benefits of long-term bisphosphonate therapy

Abstract: The benefits of long-term bisphosphonate therapy in patients at high risk of fracture likely outweigh the risks. In lower risk patients, such as those with a BMD in the osteopenic or normal range after two to five years of treatment and no history of fracture, consideration could be given to stopping therapy for two to five years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…BMD is maintained or increased if the bone had positive response to bisphosphonate [21]. Drug holiday is suggested in the "low risk osteoporotic fracture group" patients with improvement of BMD to normal or osteopenia range, no further fracture history, and good adherence to bisphosphonate for at least 2 years [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…BMD is maintained or increased if the bone had positive response to bisphosphonate [21]. Drug holiday is suggested in the "low risk osteoporotic fracture group" patients with improvement of BMD to normal or osteopenia range, no further fracture history, and good adherence to bisphosphonate for at least 2 years [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Drug holidays can be considered for patients who have been treated with bisphosphonate therapy for 5 years who have a stable bone density and no fractures [15]. The beneWts of long-term bisphosphonate therapy outweigh the risks in patients at high risk of fracture [16]. One study assessing the risk and time course of oral bisphosphonate-induced osteonecrosis of the jaws revealed that bone remodeling increased if the oral bisphosphonate was discontinued [17].…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that bisphosphonates provide some residual antifracture effect after being stopped and this effect appears to be maintained for 25 years after stopping the drug [Schmidt et al 2010]. More research is necessary to establish the significance of supersuppression of bone turnover by bisphosphonate therapy [Chaiamnuay and Saag, 2006].…”
Section: Bisphosphonates and Renal Impairmentmentioning
confidence: 99%